Intrinsic toughness of the bulk-metallic glass Vitreloy 105 measured using micro-cantilever beams. (15th January 2020) - Sorensen, Daniel; Hintsala, Eric; Stevick, Joseph; Pischlar, Jesse; Li, Bernard; Kiener, Daniel; Myers, Jason C.; Jin, Hui; Liu, Jia; Stauffer, Douglas; Ramirez, Antonio J.; Ritchie, Robert O.
Abstract: Bulk-metallic glasses (BMGs) are a class of structural materials with many attractive processing features such as the ability to be processed into parts with fine features, dimensional precision, and repeatability; however, their fracture behavior is complex and size-dependent. Previous work has shown that BMGs can display strong size effects on toughness, where multiple mechanisms on different length-scales, e.g ., crack bridging and bifurication, shear band spacing and length, can significantly affect the properies. This length-scale dependence on the fracture toughness has importance not only for advancing the understanding of fracture processes in these materials, but also for the potential future applications of BMGs, such as for microdevices. Here, using in situ scanning electron microscopy (SEM), we report on notched micro-cantilever bending experiments to address the lack of data regarding fracture properties of BMGs at the microscale. Sudden catastrophic propagation of shear bands resulted in failure for these specimens at stress intensities much lower than the bulk material, which may be due to a lack of extrinsic toughening mechanisms at these dimensions. This is explored further with post mortem SEM and transmission electron microscopy (TEM) analysis of the fractured beams while the fracture toughness results are verified using finite element modeling. The excellent agreement between model and micro cantilever beam bending experiments suggests that the intrinsic fracture toughness of Vitreloy 105, 9.03±0.59 MPa.m ½, is being reported for the first time. Graphical abstract: Image, graphical abstract